(untitled) (Research, Society and Development, 2018)
The growth of the economy contributes to the development of productive processes, increasing, consequently, the generation of waste, which in turn demand an adequate management to minimize the negative impacts involving its disposition in the environment. Thus, this work aimed to analyze the destination of industrial solid waste in the State of Minas Gerais between the years 2011 and 2016. For this, a quantitative approach was used, using documentary research based on the Inventories of Disposal of Industrial Solid Waste of Minas Gerais prepared by the State Foundation for the Environment (FEAM), for the years 2011 to 2016. There was a reduction in the amount of waste generated, from about 210.9 million tons in 2011 to 49.3 million tons in 2016. It was noticed that the most used forms of destination were the Fertigation, Boiler, External Reutilization, Internal and External Recycling, Reject Dam and Incorporation in agricultural soil. In this context, the importance related to the proper understanding of the productive process, its negative impacts and the continuous search for strategies and actions that minimize these effects are highlighted, aiming at compliance with the current legislation and the reuse of materials.